Pengaruh Struktur Modal, Profitabilitas, dan Biaya Operasional terhadap Pajak Penghasilan Terutang Badan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2015- 2017 - Dian Sulistyorini Wulandari; Mey Anjelika (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2021)
ABSTRACT The purpose of this study was to determine the effect of Capital Structure, Profitability, and Operational Costs on Corporate Income Tax. Sampling in this study, using purposive sampling method. The sample in this study consisted of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015- 2017 period, amounting to 37 companies. The analysis technique used is analysis multiple linear regression. The results of this study partially indicate that capital structure (LDAR) has no significant effect on corporate income tax, profitability (GPM) has a negative and significant effect on corporate income tax, and operational costs have a positive and significant effect on corporate income tax. Simultaneously, capital structure (LDAR), profitability (GPM), and operational costs have a significant effect on corporate income tax payable. Keywords : Longterm Debt to Asset Ratio, Gross Profit Margin, Operating Cost, Corporate income tax